Comparative evaluation of surface changes in four Ni–Ti instruments with successive uses – An SEM study - Subha, N (Medknow Publications, 2011)
AIM: To evaluate the surface alterations seen in four kinds of Nickel–Titanium (Ni–Ti) instruments using a scanning electron microscope (SEM) for five successive uses in preparing root canals of extracted human molars and also to determine whether the design of the instrument influenced the appearance of defects on the instrument surface. MATERIALS AND METHODS: Four different types of instruments namely; ProFile, ProTaper Rotary, ProTaper Hand and K3 Endo were used in 300 mesio-buccal canals. The instruments were examined under the SEM, after every use, to assess the progress of changes on their surfaces for a maximum of five uses. STATISTICAL ANALYSIS USED: Chi-square test. RESULTS: The most prevalent defects observed were pitting, followed by metal strips. Signs of discontinuity, microfractures and disruption of cutting edge were also evident. Number of defects increased with successive uses. CONCLUSIONS: ProTaper Hand showed significantly more microfractures and metal strips than other instruments from third use onwards. ProTaper Rotary and K3 Endo also showed significant changes.